Steganography on MP3 Audio files to secure messages using the Least Significant Bit (LSB) and Advanced Encryption Standard (AES) methods - Blanco, Steven; Budiman, Adam Arif (Journal TIFDA (Technology Information and Data Analytic), 2025)
The E-budgeting file code delivery system is one of the right choices for a company to send and store large amounts of data neatly and properly. Currently, Bank XYZ has not yet implemented an Android-based file delivery and storage system, resulting in difficulties in locating previously sent files. To address this issue, Bank XYZ has developed an E-budgeting file code delivery system. This system is Android-based and operates using Android smartphones online. It is also designed to securely store files using AES (Advanced Encryption Standard) encryption and LSB (Least Significant Bit) steganography methods. The purpose of the E-budgeting file code delivery system is to facilitate the secure transmission of these codes to the relevant parties